Isolasi Fungi Asal Rawa Lebak Untuk Bioremediasi Air Rawa Tercemar Bahan Organik - Ade Bayu Saputra; Marini Wijayanti; Dade Jubaedah (Jurnal Akuakultur Rawa Indonesia, 2019)
Aquaculture sometimes only depends on water absorption without water exchange therefore the accumulation of organic material give impact on water quality in aquaculture and cause illness and death of fish. Fungi have many variations in water that can be selected by isolation and identification to maintain water quality swamp cultured. This research aims to get swamp fungi isolates as candidate bioremediator of swamp water contaminated with organic matter. Research was conducted from December 2016 to April 2017 in Laboratory of Microbiology, Department of Biology, Faculty of Science and Mathematics, Sriwijaya University and Basic Laboratory of Fisheries, Department of Aquaculture, Faculty of Agriculture, University of Sriwijaya. The methods of research started from isolation and selection of fungi, analysis of isolates capability to improve the quality of black water, and observations of swamp water quality.This research method started from isolation and selection lipolytic, cellulolytic, proteolytic fungi, the test isolates ability to improve swamp water quality and observation of water swamp quality. Monitoring  of  water  quality done  at  the sampling time, beginning and end of the research, including pH, temperature, ammonia and TDS. The results showed that the best fungi growth rate in contaminated swamp water of organic matter was 93%.day-1. Fungi isolates are able to play a role in the ammonification of bioremediation process.